2012
DOI: 10.1172/jci63782
|View full text |Cite
|
Sign up to set email alerts
|

Restoring balance to B cells in ADA deficiency

Abstract: It is paradoxical that immunodeficiency disorders are associated with autoimmunity. Adenosine deaminase (ADA) deficiency, a cause of X-linked severe combined immunodeficiency (SCID), is a case in point. In this issue of the JCI, Sauer and colleagues investigate the B cell defects in ADA-deficient patients. They demonstrate that ADA patients receiving enzyme replacement therapy had B cell tolerance checkpoint defects. Remarkably, gene therapy with a retrovirus that expresses ADA resulted in the apparent correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our unpublished results showed that ADA has a suppressive effect on Foxp3 + T cell; conceivably, a low Foxp3 + T cell activity offsets the suppressive effect of ADA on Th1 responses. These results agree with previous reports showing that both adenosine and ADA interfere with regulatory T cell function (35; 44; 45). Because of previous concerns that prolonged ADA treatment is more likely to cause immune dysregulation (4), we looked at the therapeutic effect of a single injection of ADA and found that a single, appropriately timed injection could be effective.…”
Section: Discussionsupporting
confidence: 93%
“…Our unpublished results showed that ADA has a suppressive effect on Foxp3 + T cell; conceivably, a low Foxp3 + T cell activity offsets the suppressive effect of ADA on Th1 responses. These results agree with previous reports showing that both adenosine and ADA interfere with regulatory T cell function (35; 44; 45). Because of previous concerns that prolonged ADA treatment is more likely to cause immune dysregulation (4), we looked at the therapeutic effect of a single injection of ADA and found that a single, appropriately timed injection could be effective.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, ADA plays an essential role in the establishment of early B-cell tolerance and the removal of developing autoreactive B cells in humans (Luning Prak, 2012; Sauer et al, 2012b). …”
Section: New Insights Into Immune Cell Dysfunction and Onset Of Autoimentioning
confidence: 99%
“…Strikingly, ADA-deficient patients treated with HSC-GT displayed quasi-normal early B-cell tolerance checkpoints as evidenced by restored efficient removal of developing autoreactive and anti-nuclear B cells. Hence, ADA plays an essential role in the establishment of early B-cell tolerance and the removal of developing autoreactive B cells in humans (Luning Prak, 2012 ; Sauer et al, 2012b ).…”
Section: New Insights Into Immune Cell Dysfunction and Onset Of Autoimentioning
confidence: 99%
See 2 more Smart Citations